Theoretical Model and Practical Pathway for Digital Transformation of Classroom Teaching in Health Education Using Big Data Technology - Haoyu Wang (Engineering Proceedings)
This study aims to reveal the characteristics of the digital transformation of classroom teaching in health education. The key links of the digital transformation process in classroom teaching were identified to determine an implementation pathway. Based on the results, theoretical and practical guidance for the implementation of digital transformation in health education was proposed.